Exploring cognitive risk and protective factors of shattered assumptions and pandemic induced distress in Filipino college students - Carpio, Jennifer Gay E. (Animo Repository, 2021)
The challenges of the COVID-19 pandemic are expected to weaken worldviews and core beliefs, increasing vulnerability to pathological outcomes. However, variability in trauma outcome indicates possible risk and protective factors that influence the shattering of worldviews and reduce the prevalence of negative posttrauma conditions. In a survey of college students, Study 1 examined core belief disruption as a risk factor to the shattering of worldviews and development of adverse trauma outcomes (depression, anxiety, peritraumatic distress). A mediation analysis revealed that only worthiness of the self significantly mediated the indirect relationship between core belief disruption and all posttrauma outcomes. Further, core belief disruption positively influenced worldviews, a deviation from the hypothesis that worldviews weaken when core beliefs are challenged. Study 2 examined locus-of-hope (LOH) as protective factors against the negative effect of disrupted core beliefs and shattered worldviews on all three outcomes. External-spiritual LOH significantly moderated the indirect effect of core belief disruption on all outcomes mediated by benevolence. External-family LOH also significantly moderated the indirect relationship with benevolence as mediator and peritraumatic distress as the outcome. Further, internal LOH significantly moderated the direct effect of core belief disruption on peritraumatic distress. Significant external and internal LOH dimensions demonstrated differing moderating effects, with external dimensions exerting an amplifying effect while internal LOH exhibited a buffering effect. Overall, both internal and external LOH dimensions, as well as worthiness of the self, function as protective factors that promote adaptive coping and prevents the exacerbation of adverse psychological conditions in college students. Keywords: worldviews, locus-of-hope, core beliefs, trauma, distress, anxiety, depression, COVID-19 pandemic